The Advisory Position of State Council and its Roles within the Framework of Administrative Contracts - Karim, Zana Raof Hama; Rashid, Awaz halid Mohammed (Journal of Legal and Political Studies, 2021)
The advisory position constitutes one of the two essential pillars of function which state councils undertake in countries with dual judiciary in addition to the judicial position, and by virtue of this position the council appears as a legal advisor to the state who provides it with legal opinions that illuminate its legal path, and settle whatever disputes may arise between its departments, it also contributes to draft or enact draft laws related to public administration. Advisory opinion within the context of administrative contracts, is meant to mean any procedures whereby the competent administrative authority is concluding a contract in order to obtain consultation or legal opinion from another agency or administration which is usually called advisory body advisory administration, before concluding the contract, and for the technical, financial or legal considerations, the legislature may impose the administration wishing to enter into the contractual process by requesting an advisory opinion.
Keywords: advisory position; judicial position; public administration; consultation; administrative authority